Dietary Nutrients and Male Infertility: Review of Current Evidence: - Hosseini, Banafshe; Djafarian, Kurosh (Galen Medical Journal, 2015)
Lifestyle factors and nutritional status are regarded as critical determinants of normal reproductive function. Hence, the role of dietary nutrients has attracted the attention of researchers to the extent that some studies have addressed the effects of diet on the risk of male infertility. This study aimed to summarize the literature regarding the association between various dietary factors and male infertility. Literature searching for studies on male infertility and nutrition, published between January 1982 and May 2015, was performed using PubMed and Scopus databases. The bibliographies of included studies were also searched for additional references. About 65 articles were identified and after the elimination of irrelevant studies, 35 related studies available for review were examined. Studies have indicated that in men with idiopathic infertility, omega-3 intervention resulted in significant improvement in total sperm count as well as sperm cell density. Moreover, several studies have shown that higher intake of poultry, cereals, fruit and vegetables may play a beneficial role in male infertility; although, some studies have not attained such results. Taken as a whole, studies demonstrated that food consumption may play a major role in preventing or facilitating male infertility. Further studies are needed to clarify this association. [GMJ.2015;4(4):123-29]